1985
DOI: 10.1172/jci112193
|View full text |Cite
|
Sign up to set email alerts
|

Independent modulation of von Willebrand factor and fibrinogen binding to the platelet membrane glycoprotein IIb/IIIa complex as demonstrated by monoclonal antibody.

Abstract: In this study we have used two new monoclonal antibodies, designated LIP5 and LJP9, as well as a previously described one, AP2, all specific for the platelet membrane glycoprotein (GP)IIb/ IIIa complex. None of them reacted with dissociated GPIIb or GPIIIa. The monovalent Fab fragment of both LJP5 and LJP9 bound to unstimulated platelets in a saturable manner, but binding was markedly decreased after platelets had been incubated at 370C in the absence of added extracellular calcium. The binding of LJP9 was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(37 citation statements)
references
References 50 publications
4
33
0
Order By: Relevance
“…The inhibition by these peptides also suggests that these adhesive proteins share a common binding site on the activated I1 bIIIa complex. However, data mentioned in this study and those recently reported by Trapani Lombardo et al [47] show that monoclonal antibodies can specifically inhibit fibronectin or vWf binding to stimulated platelets without affecting fibrinogen binding or platelet aggregation. Plow et al 1451 have recently suggested that high-affinity interactions of any of these four adhesive proteins with platelets may call for common as well as unique binding sites.…”
supporting
confidence: 55%
“…The inhibition by these peptides also suggests that these adhesive proteins share a common binding site on the activated I1 bIIIa complex. However, data mentioned in this study and those recently reported by Trapani Lombardo et al [47] show that monoclonal antibodies can specifically inhibit fibronectin or vWf binding to stimulated platelets without affecting fibrinogen binding or platelet aggregation. Plow et al 1451 have recently suggested that high-affinity interactions of any of these four adhesive proteins with platelets may call for common as well as unique binding sites.…”
supporting
confidence: 55%
“…Accordingly, this antibody inhibited 1251I-vWF binding to normal or afibrinogenemic platelets stimulated by ADP plus adrenaline (Table I). In previous studies we have shown that antibody UPS has no effect on the binding of fibrinogen to GPIIb/IIIa (see reference 24 for full details). Moreover, antibody UP5 has no effect on the aggregation of normal platelet-rich plasma (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…belong to three different kindreds and have been previously described in detail (19-2 1 Monoclonal antibody. The anti-GPIIb/IIIa monoclonal antibody UP5 has been recently described in detail (24). It blocks vWF binding to stimulated platelets without affecting fibrinogen binding.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations